Calcium Oxalates in Soils within Disturbed Landscapes and Rock on the Territory of Yakutia (Russia), Formation Conditions in a Sharply Continental Cryoarid Climate - Tatiana I. Vasileva; Yana B. Legostaeva (Minerals, 2023)
The formation of oxalates in soils and rocks under conditions of cryoarid climate, permafrost and taiga vegetation was studied. Whewellite and weddellite were found in four areas associated with the mining industry: on the kimberlite deposit of the Daldyn territory, in the lower reaches of the Markha River of the Central Yakut Plain, and on the coastal outcrop of the Allah-Yun Sellah-Khotun ore cluster. Whewellite was found in the upper organic horizon of Skeletic Cryosol (Thixotropic) (sample 151) and as a film on the surface of plant remains of Humic Fluvisols (sample 1663). Weddellite was found as an extensive encrustation on the surface of the soil and vegetation cover of Stagnic Cryosols Reductaquic (sample 984) and on a siltstone outcrop (sample KM-6-21). Calcium oxalates were identified by X-ray phase analysis, photographs of the samples were taken on a polarizing microscope, and the crystal morphology was studied on a scanning electron microscope. To determine the chemical composition of soils and rocks, the classical wet-chemical method was used; the physical properties of the studied samples were studied using a pH meter, the photoelectric colorimetric method, and a synchrotron thermal analysis device. The source of calcium for the formation of salts is the parent layers of the studied soils, represented by carbonate and carbonate clastic rocks, which cause neutral and slightly alkaline environments. High humidity, which is provided by the seasonal thawing of the permafrost, has a key role in the formation of the studied oxalates in Yakutia with a sharply continental cryoarid climate. Based on the studies, it was found that the first two samples are the products of lichen activity, and the third and fourth are at the stage of initial soil formation by micromycetes. In addition, the formation of these oxalates, in our opinion, is the result of the protective function of vegetation, in the first two cases, with a sharp increase in the load on lichens under technogenic impact, and in the second and third ...